10 Evaluating a nurse led triage process in treating patients with left bundle branch block (LBBB) referred for primary percutaneous coronary intervention (pPCI). (9th June 2011) - Joshi, N V; Bawamia, B R; Jamieson, S; Zaman, A; Edwards, R
Abstract : Background: The Freeman Hospital (FRH) performs over 900 pPCI a year. Patients with suspected Acute Myocardial Infarction (AMI) are referred either by paramedics or networked hospitals for consideration of pPCI via a Telmed system, which is triaged by experienced CCU nurses. The pPCI Pathway can be activated in patients with LBBB suspected of having an AMI. However, there remains considerable variation in the clinical utility of new or presumed new LBBB as a ST-elevation myocardial infarction (STEMI)-equivalent ECG diagnostic criterion. The major discriminators the triage staff use in this population are ECG findings and symptoms suggestive of AMI. Our aim was to evaluate outcomes in patients with LBBB accepted to FRH or referred to local hospitals for assessment. Methods: Consecutive patients referred to FRH with LBBB and suspected AMI from 1st August 2009 to 30th November 2009 were analysed by recording: 1) Peak Troponin Level 2) Angiographic findings 3) Revascularisation rates. Results: 1069 patients were referred for consideration of pPCI. 177 (16.6%) of patients had new or presumed new LBBB. 33 (18.6%) patients were accepted by FRH and 144 patients (81.4%) were declined and referred to their local hospitals for assessment. Abstract 10 Table 1 Troponin levels in patients with LBBB referred for consideration of pPCI. 26.5% of patients with LBBB referred for consideration of pPCI had moderately to highly raised troponin. Of the 33 patients admitted to FRH, 13 underwent inpatient angiography and 9 patients had significant coronary disease (coronary stenosis 70%–100% in at least one coronary artery). Of those, 5 had PCI and 1 required urgent CABG. Only one patient had a 100% coronary occlusion believed to be an acute occlusion. 4 patients had unobstructed coronaries and were managed medically. Of the 132 patients declined for pPCI only 2 (1.5%) were referred back to FRH for PCI. Neither of these patients was found to have a 100% acute occlusion of a coronary artery. Conclusion: Revascularisation was performed in only 6/33 (18.2%) accepted for assessment and only 2/132 (1.5%) were referred back to the centre for PCI. The sensitivity of the triage process in detecting patients with LBBB requiring urgent revascularisation is 75% and the specificity is 83%. The sensitivity of detecting patients with an acutely occluded artery diagnosed at angiography is 100% with a specificity of 81%. In a high volume Heart Attack Centre a nurse led triage is effective at discriminating patients with LBBB requiring immediate coronary intervention.